Clinical features and gastric myoelectrical activity in patients with idiopathic and post‐surgical rapid gastric emptying who present with unexplained chronic nausea. Issue 3 (18th September 2020) - Wang, Patty T.; Wellington, Jennifer; Koch, Kenneth L.
Abstract: Background: The cause of chronic nausea can be difficult to diagnose. Idiopathic rapid gastric emptying (iRGE) can cause nausea, but limited literature exists on clinical and pathophysiological features. In contrast, dumping syndrome or post‐surgical rapid gastric emptying (psRGE) is well‐known and may present with early phase vasomotor symptoms, diarrhea, and late phase reactive hypoglycemia. Our aim is to compare clinical and gastric motility characteristics in patients with iRGE and psRGE and unexplained chronic nausea. Methods: A retrospective study was conducted on patients with unexplained chronic nausea and RGE (<30% retention of a standard isotope‐labeled solid meal at 1‐h). Gastric myoelectrical activity (GMA) was recorded during water load satiety tests (WLST) using validated electrogastrogram (EGG) recording methods. Key Results: Thirty iRGE and sixteen psRGE patients with unexplained chronic nausea were identified; average 1‐hour meal retention was 18.6% and 16.2%, respectively. Nausea, bloating, early satiety, and bowel function were similar in the two groups; fewer iRGE patients had abdominal pain and none had vasomotor symptoms. Normal 3 cpm GMA was recorded in 44% of iRGE vs 29% of psRGE, tachygastria in 13% vs 43%, bradygastria in 25% vs 14%, and mixed in 19% vs 14% ( p values >0.05). Abnormal WLST volume (<300 ml) was found in 69% of iRGE and 43% of psRGE ( p = 0.36). Conclusions & Inferences: (a) iRGE and psRGE patients may present with unexplained chronic nausea rather than classic vasomotor symptoms and diarrhea. (b) iRGE and psRGE patients had similar gastric dysrhythmias and accommodation dysfunction, which may contribute to RGE.